Partitioning multiple facets of beta diversity in a tropical stream macroalgal metacommunity - Branco, Ciro C. Z. [UNESP]; Bispo, Pitágoras C. [UNESP]; Peres, Cleto K.; Tonetto, Aurélio F.; Krupek, Rogério A. [UNESP]; Barfield, Michael; Holt, Robert D. (Wiley, 2020)
Aim: We evaluated different facets of beta diversity (taxonomic, phylogenetic and functional), and its components (spatial turnover and nestedness), of a stream macroalgal metacommunity, as well as the effect of local environmental variables, types of biome and spatial factors on these facets and components. Location: Ten natural areas of southern Brazil, covering the main biomes represented in the region. Taxon: Stream macroalgae. Methods: We analysed a macroalgal data set collected in 105 stream segments using a dissimilarity partitioning approach to decompose total beta diversity into spatial turnover and nestedness components. Furthermore, we assessed the effects of local environmental variables, biome type and spatial factors on beta diversity components by performing distance-based redundancy analysis (db-RDA), and its partial version (db-pRDA). Taxonomic data were tabulated considering four different species incidence matrices: total macroalgae; only green algae; only red algae and only cyanobacteria. Results: For taxonomic and phylogenetic facets, very high values of total beta diversity were found for all species incidence matrices, with spatial turnover (species replacement) accounting for almost all this diversity; nestedness had extremely low values. For functional diversity, total beta diversity was again high and spatial turnover was greater than nestedness, but nestedness (the tendency for less diverse locations to contain a subset of those in higher diversity locations) was considerably higher than that observed for taxonomic and phylogenetic facets. In regard to taxonomic and phylogenetic facets, total beta diversity and spatial turnover were, in general, significantly related to local environmental variables, biome type and spatial factors for total macroalgae and green algae, whereas they were significantly related to types of biome and space for red algae, and only to local environment for cyanobacteria. Main conclusions: Our results showed that spatial turnover was the main component of beta diversity, regardless of the facet and macroalgal species incidence matrix, and that the relative influence of local environmental variables, types of biome and spatial factors on the total beta diversity and its spatial turnover component can vary according to the facet considered and by algal group.
Keywords: environmental heterogeneity; functional beta diversity; nestedness; phylogenetic beta diversity; spatial turnover; stream macroalgae; taxonomic beta diversity